TP1-1 Endovascular versus surgical management of pericallosal artery aneurysms, single centre experience. Issue 3 (14th February 2019) - Draz, MS; Toma, AK; Bezouich, S; Grover, P
Abstract : Objectives: Comparing surgical versus endovascular management of pericallosal artery aneurysm. Design: Retrospective case series. Subjects: Patients managed in our unit for pericallosal artery aneurysms. Methods: Patients medical and radiological records were reviewed collecting data about presentation, management, complications. Clinical outcome was assessed by mRS at 3, 6 and 12 months. Imaging were reviewed to report aneurysm size and treatment outcome. Results: Average follow up period 3.3 years SD ±3.5. 38 patients had SAH and 19 were incidentally discovered. Initial CT showed SAH in 21 patients, IVH in 3, ICH in 3 IVH and ICH in 9. 33 patients treated using endovascularly, 13 patients conservatively and 2 by surgical clipping. 33% of endovascular group had stroke caused by approach related complications. 41.3% of the patients had mRS (0–2) at 3 months period. Increased to 46.5% at 12 months. Average imaging follow up was 1.5 years (SD ±1.6). 36.3% of endovascular group showed aneurysm remnant filling or recurrence. Conclusions: Pericallosal artery aneurysms are complex in nature and both management modalities are challenging. Complications were high in endovascular group. Surgical intervention should be considered in selected patients where complex intervention is required.